Social Media as a Tool of Building Reputation and Identity of National Parks - Korená, Kristína; Pártlová, Petra (Communication Today, 2023)
Social media have turned out to be a suitable tool of marketing communication that enables the virtual connection of individual public accounts (profiles) to share information, data and create conditions for the joint implementation of activities. The submitted study focuses on the evaluation of the use of marketing communication in nine selected European national parks. The study analyses data that indicates the level of using social networking sites for presenting the official profiles and websites in the context of building reputation and identity in order to determine to what extent national parks use suitable tools of marketing communication and what are its possibilities and limitations. Marketing communication was examined using the rhetorical and descriptive analysis of text, which enabled performing a content analysis focused on three main parts: Pathos, Ethos and Logos. Within the descriptive analysis, another part of the research dealt with communication focused on the issue of education, environmental protection and business activities in the area of tourism. A new formula for calculating Social Media Effectiveness was proposed, calculated at a global level. Based on the results obtained, Plitvice Lakes National Park was rated the best, while the results in terms of marketing communication were recorded in the case of the Swiss national park, National Park Saechsische Schweiz. The main barrier to marketing communication is the reluctance to use English as the main language of communication and in the case of the Facebook platform, a higher number of posts. The results also showed that good marketing communication has an impact on the number of visitors to national parks and the right combination of published posts influences the behaviour of national park visitors. Furthermore, we confirmed the influence of communication on the possibility to educate especially the younger generation through media platforms, which is a positive finding.